THE INFLUENCE OF THE TOURISM SECTOR AND THE ABSORPTION OF MSMES ON ECONOMICS GROWTH IN THE PROVINCE OF BALI IN 2015-2019 (CASE STUDY: 9 REGENCIES/CITIES) - Rahmadhany, Nurul (Faculty of Economics and Business, Universitas Negeri Jakarta, 2021)
This study aims to determine the influence of tourism sector and absorption of MSME workforce on economic growth. The data used in each variable is secondary data on the number of foreign tourists, the number of restaurants and restaurants, the average length of stay, the absorption of MSMEs, and GDP in Bali. The data was obtained from panel data from 9 regencies/cities in Bali province namely Jembrana, Tabanan, Badung, Gianyar, Klungkung, Buleleng, Bangli, Karangasem, and Denpasar for 5 years from 2015-2019. Data analysis techniques using regression analysis using Random Effect Model based on Hausman test. The results showed that the number of foreign tourists, the number of restaurants and restaurants had a positive and significant effect on GDP. Meanwhile, for the average length of stay has a positive and insignificant effect on GDP And the absorption of msme sector labor has a negative but insignificant effect on the GDP district / city d Bali Province.